Evaluasi Penilaian Kinerja Ditinjau Dari Perilaku Kerja ASN Di Kantor Distrik Malind - Putri Inggrid Maria Risamasu; Maria Kaok (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2020)
This article aims to find out how the evaluation of employee performance appraisals in Malind district, Merauke Regency using the Employee Performance Target (SKP) system in terms of work behavior. This research is presented in descriptive qualitative form by describing and explaining in sentence form all the results contained in this research. Types of data used are primary data and secondary data sourced as well as literature studies. Data collection was carried out using field observations and in-depth interviews with the Head of Malind District as informants. The results obtained are that in Malind district, Merauke Regency, the implementation of performance appraisal evaluations has generally been running according to established procedures, but there are still some weaknesses, including in terms of discipline from the employees themselves which have an impact on service orientation to the public. Then the weak attitude of integrity shown by employees so that in determining work targets has not shown maximum results. The conclusion of this research is that performance appraisal evaluation is a mandatory procedure that must be done so that employees can know their job duties and responsibilities. The process of determining performance measures must be considered and adjusted, because performance indicators will be used to measure the level of progress of employees in their work, individually or in teams.